Educational mismatch and labour mobility in the hospitality industry in Andalusia - Andrés J. Marchante; Bienvenido Ortega; José Luis Sánchez-Ollero (European Regional Science Association (ERSA), 2003)
The objectives of this paper are to analyse the determinants of educational mismatch and the effect of overeducation on workers' occupational mobility. With these aims, a cross-section of 3,314 workers from the hospitality sector in Andalusia has been used. The econometric analyses shows that workers can compensate for their shortfall in education with greater amounts of experience and/or on-the-job training. Likewise, our results indicate that educational mismatch has not impact on workers' occupational mobility.
Keywords: 330